2011
DOI: 10.1007/s10532-011-9484-y
|View full text |Cite
|
Sign up to set email alerts
|

Microbial degradation of microcystin in Florida’s freshwaters

Abstract: Presence of microcystin (MC), a predominant freshwater algal toxin and a suspected liver carcinogen, in Florida’s freshwaters poses serious health threat to humans and aquatic species. Being recalcitrant to conventional physical and chemical water treatment methods, biological methods of MC removal is widely researched. Water samples collected from five sites of Lake Okeechobee (LO) frequently exposed to toxic Microcystis blooms were used as inoculum for enrichment with microcystin LR (MC-LR) supplied as sole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 32 publications
3
28
0
1
Order By: Relevance
“…3a and b). Only a few genera capable of degrading MCLR fall into these two phyla (Liu et al, 2007;Manage et al, 2009;Alamri et al, 2010;Ramani et al, 2012), but these genera were all detected at low abundance here, and further declined or even disappeared on day 7 (Table 3). A probable reason for this phenomenon was that these genera suffered from competition against the strongly growing Proteobacteria population, which might compromised the participation of these genera in MCLR-biodegradation process in sediment.…”
Section: Shifts Of Composition Profile In Response To Sediment-mediatmentioning
confidence: 68%
“…3a and b). Only a few genera capable of degrading MCLR fall into these two phyla (Liu et al, 2007;Manage et al, 2009;Alamri et al, 2010;Ramani et al, 2012), but these genera were all detected at low abundance here, and further declined or even disappeared on day 7 (Table 3). A probable reason for this phenomenon was that these genera suffered from competition against the strongly growing Proteobacteria population, which might compromised the participation of these genera in MCLR-biodegradation process in sediment.…”
Section: Shifts Of Composition Profile In Response To Sediment-mediatmentioning
confidence: 68%
“…and Sphingomonas sp. have been reported to be capable of utilizing and degrading microcystin [25]. Hydrogenophaga has been reported to be an algicidal bacterium against harmful algae bloom [9].…”
Section: Resultsmentioning
confidence: 99%
“…Microbial biodegradation is an environmentally-friendly and effective treatment method for detoxify MC-LR in natural waters without potential harmful by-products. Some MC-degrading pure bacterial strains have been isolated and have their MC-LR-degrading rates reported [6, 16, 17, 19]. For example, the single pure bacterial strain Sphingomonas sp.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous investigations demonstrated that microbial biodegradation may be one of the most environmentally-friendly, effective and promising treatment methods for removing MC-LR in natural waters, since it can detoxify MC-LR and don’t generated any apparent potential harmful by-products [3, 6, 14-17]. A few MC-degrading pure bacterial strains have been isolated, identified and had their mechanisms reported, and most of the isolated MC-degrading bacteria were limited to the family Sphingomonadaceae [16-18]. In practice, native bacterial communities (indigenous bacterial mixed culture) may be more suitable for degrading MC-LR in the environment compared to the single pure bacterial strains [6,19].…”
Section: Introductionmentioning
confidence: 99%